Attitudes and perceptions of health professionals towards management of hypothyroidism in general practice: a qualitative interview study. Issue 2 (21st February 2018) - Dew, Rosie; King, Kathryn; Okosieme, Onyebuchi E; Pearce, Simon H; Donovan, Gemma; Taylor, Peter N; Hickey, Janis; Dayan, Colin M; Leese, Graham; Razvi, Salman; Wilkes, Scott
Abstract : Objective: To explore the attitudes and perceptions of health professionals towards management of hypothyroidism that contributes to the suboptimal treatment of hypothyroidism in general practice. Design: A qualitative interview study using semistructured interviews. Participants: Sixteen participants were interviewed between March and August 2016 comprising nine general practitioners (GPs), four pharmacists, two practice nurses and one nurse practitioner. Setting: General practice and community pharmacies in the counties of Northumberland, Tyne and Wear, Stockton-on-Tees and North Cumbria, North of England, UK. Method: A grounded-theory approach was used to generate themes from interviews, which were underpinned by the theory of planned behaviour to give explanation to the data. Results: Although health professionals felt that hypothyroidism was easy to manage, GPs and nurses generally revealed inadequate knowledge of medication interactions and levothyroxine pharmacokinetics. Pharmacists felt limited in the advice that they provide to patients due to lack of access to patient records. Most GPs and nurses followed local guidelines, and relied on blood tests over clinical symptoms to adjust levothyroxine dose. The information exchanged between professional and patient was usually restricted by time and often centred on symptoms rather than patient education. Health professionals felt that incorrect levothyroxine adherence was the main reason behind suboptimal treatment, although other factors such as comorbidity and concomitant medication were mentioned. Enablers perceived by health professionals to improve the management of hypothyroidism included continuity of care, blood test reminders, system alerts for interfering medications and prescription renewal, and accessible blood tests and levothyroxine prescriptions for patients. Conclusion: There is a significant health professional behavioural component to the management of hypothyroidism. Addressing the differences in patient and professional knowledge and perceptions could reduce the barriers to optimal treatment, while continuity of care and increased involvement of pharmacists and practice nurses would help to promote optimal thyroid replacement.